2005
DOI: 10.1124/jpet.105.087619
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Capsaicin-Stimulated Secretion in the Stomach: Comparison with Mucosal Acidification

Abstract: The effects of capsaicin and mucosal acidification on gastric HCO 3 Ϫ secretion were compared in wild-type and prostacyclin (PGI 2 ) IP receptor or prostaglandin E receptor EP1 or EP3 knockout C57BL/6 mice as well as rats. Under urethane anesthesia, the stomach was mounted on an ex vivo chamber, perfused with saline, and the secretion of HCO 3 Ϫ was measured at pH 7.0 using the pH-stat method. Capsaicin or 200 mM HCl was applied to the chamber for 10 min. Capsaicin increased the secretion of HCO 3 Ϫ in rats an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 41 publications
(62 reference statements)
1
35
0
Order By: Relevance
“…Indeed, we observed that the isolated stomach generated NO under basal conditions without any treatment and that the production was significantly reduced by the serosal addition of L-NAME. Consistent with our previous findings (Aihara et al, 2005a), we further observed in this study that NOR-3 stimulated HCO 3 Ϫ secretion in the stomach, partly mediated by endogenous PGs and through the activation of EP1 receptors. Thus, it is assumed that the inhibition of PDE1 and PDE5 first increases intracellular levels of cGMP and then stimulates gastric HCO 3 Ϫ secretion in two ways, directly via cGMP and indirectly mediated by PGE 2 /EP1 receptors.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Indeed, we observed that the isolated stomach generated NO under basal conditions without any treatment and that the production was significantly reduced by the serosal addition of L-NAME. Consistent with our previous findings (Aihara et al, 2005a), we further observed in this study that NOR-3 stimulated HCO 3 Ϫ secretion in the stomach, partly mediated by endogenous PGs and through the activation of EP1 receptors. Thus, it is assumed that the inhibition of PDE1 and PDE5 first increases intracellular levels of cGMP and then stimulates gastric HCO 3 Ϫ secretion in two ways, directly via cGMP and indirectly mediated by PGE 2 /EP1 receptors.…”
Section: Discussionsupporting
confidence: 81%
“…Furukawa et al (1999Furukawa et al ( , 2000 showed that the secretion of HCO 3 Ϫ in isolated duodenum in vitro was stimulated by NOR-3, at least partly, via production of PGE 2 through activation of COX-1. We also showed that NOR-3 also increased PGE 2 production in the rat stomach, resulting in stimulation of HCO 3 Ϫ secretion (Aihara et al, 2005a). The levels of cGMP in the isolated mouse stomach were also significantly increased by NOR-3.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…O 2 − , superoxide; H 2 O 2 , hydrogen peroxide; ONOO, peroxynitrite; N2O 3 B2 receptor antagonists also exert a protective effect in the postischemic intestine (465). Bradykinin, PAF and LTB4 are involved in the early immediate recruitment of neutrophils and appear to mediate this effect largely through transcription-independent mechanisms (160,467).…”
Section: Consequences and Mechanisms Of Ischemic Injurymentioning
confidence: 97%
“…The submucosal arterioles branch into capillaries at the base of the glands and postcapillary vessels pass to the luminal surface of the mucosa where they form another capillary network surrounding the gastric pits (147). This seriescoupled arrangement allows for the HCO 3 − released from the parietal cell during H + secretion to be delivered to the basal side of the mucosal surface cells (Fig. 1).…”
Section: Salient Features Of the Mucosal Microcirculationmentioning
confidence: 98%